Sericulture – The Main Occupation of The Ferghana Valley Population - Madraximov Zoxid Sharofovich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The article discusses sericulture, which was the main occupation of the population of the Ferghana Valley in the 18th and early 19th centuries. It highlights the silk and silk products produced in the major economic centers—Kokand, Namangan, Andijan, Margilan, and Osh—along with their significance in the internal and external trade of the country.